1980
DOI: 10.1002/pros.2990010205
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of prostatic carcinoma among blacks: A comparison between a low‐incidence area, Ibadan, Nigeria, and a high‐incidence area, Washington, DC

Abstract: A comparison of carcinoma of the prostate gland in a low-incidence Nigerian (Ibadan) population and a high-incidence U.S. Afro-American (Washington, D.C.) population was the purpose for this study, initiated in 1973. The frequency of carcinoma (micro- and invasive) was determined in consecutive necropsy cases from hospitals in Ibadan, Nigeria, Accra, Ghana and Washington, D.C. The results of these clinical, epidemiologic and morphologic studies are reported. Clinically, the peak incidence of carcinoma of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
1

Year Published

1983
1983
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 41 publications
4
19
1
Order By: Relevance
“…It is unlikely that workers in book keeping, finance, and insurance are exposed to occu pational carcinogens, but higher than average expo sure to life-style related risk factors (e.g., particular dietary habits) might be possible. Lack of occupa tional physical exertion might be a potential risk fac tor for prostate cancer, but study results concerning this factor have been conflicting so far [28,29]. In our study no other categories of "white collar" workers have been found with an increased risk for prostate cancer.…”
Section: Discussioncontrasting
confidence: 63%
“…It is unlikely that workers in book keeping, finance, and insurance are exposed to occu pational carcinogens, but higher than average expo sure to life-style related risk factors (e.g., particular dietary habits) might be possible. Lack of occupa tional physical exertion might be a potential risk fac tor for prostate cancer, but study results concerning this factor have been conflicting so far [28,29]. In our study no other categories of "white collar" workers have been found with an increased risk for prostate cancer.…”
Section: Discussioncontrasting
confidence: 63%
“…Cigarette smoking has not been associated with increased risk of prostate cancer in most previous epidemiologic studies (Hammond, 1966;Doll & Peto, 1976;Wynder et al, 1971;Armenian et al, 1975;Jackson et al, 1980). Although the majority of these studies were hospital-based case-control studies and used controls who were not screened for diseases potentially associated with smoking, most cohort studies which have examined this relationship also have been negative.…”
Section: Resultsmentioning
confidence: 99%
“…If so, this might be of influence since it is suspected that dietary factors contribute significantly to the occurrence of prostate cancer [86,87]. Perhaps physical exertion (at work and during leisure time) is associated with prostate cancer risk, but study results dealing with this factor are conflicting [66,88]. So far the role of other life-stylerelated factors is largely unclear.…”
Section: Discussionmentioning
confidence: 99%